2002
DOI: 10.1590/s0036-46652002000300004
|View full text |Cite
|
Sign up to set email alerts
|

Snakebites by Crotalus durissus ssp in children in Campinas, São Paulo, Brazil

Abstract: From January, 1984 to March, 1999, 31 children under 15 y old (ages 1-14 y, median 8 y) were admitted after being bitten by rattlesnakes (Crotalus durissus ssp). One patient was classified as "dry-bite", 3 as mild envenoming, 9 as moderate envenoming and 18 as severe envenoming. Most patients had neuromuscular manifestations, such as palpebral ptosis (27/31), myalgia (23/31) and weakness (20/31). Laboratory tests suggesting rhabdomyolysis included an increase in total blood creatine kinase (CK, 28/29) and lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
2
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 19 publications
6
65
2
8
Order By: Relevance
“…Its importance as an emergency medical condition is high among children. Although case series from the USA, South America, Australia and Asia have reported children with snakebites, they show different snake species from Taiwan (17)(18)(19)(20)(21)(22). In addition, high mortality and functional impairment of extremities after bites were found in some studies due to delayed hospital visits and limited antivenom use (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…Its importance as an emergency medical condition is high among children. Although case series from the USA, South America, Australia and Asia have reported children with snakebites, they show different snake species from Taiwan (17)(18)(19)(20)(21)(22). In addition, high mortality and functional impairment of extremities after bites were found in some studies due to delayed hospital visits and limited antivenom use (14,16).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Although no significant difference was present between the AKI and non-AKI groups, a possible factor related to the development of renal injury might be the administration of less antivenom in the AKI group. In the literature, it has been shown that early administration of antivenom reverses clinical manifestations of snakebite.…”
Section: Risk Factors For Development Of Arfmentioning
confidence: 99%
“…Exames seqüenciais para avaliação dos pares cranianos não detectaram, em nosso experimento, nenhum sinal de acometimento dos seus núcleos, como por exemplo abolição do reflexo pupilar, "fácies neurotóxico de Rosenfeld" e o nistágmo verificados em humanos (Barraviera 1999, Pinho& Pereira 2001, Bucaretchi et al 2002, animais de laboratório (Castro 1999) e em cães (Ferreira Júnior & Barraviera 2004, Nogueira et al 2004) ou ainda, a ptose palpebral, verificada em alguns experimentos com bovinos (Belluomini et al 1982, Lago 1996. Por outro lado, constatamos a paralisia do globo ocular, em todos os animais que receberam doses de 0,015 ou 0,03mg/kg, revelada através da não-exposição da esclera durante a rotação da cabeça no sentido horário e antihorário, alteração descrita por Belluomini et al (1982) Este achado clínico constitui, ao nosso ver, indicação importante para estabelecimento do diagnóstico e diagnóstico diferencial do envenenamento crotálico em bovinos.…”
Section: Quadro Neurológicounclassified
“…Além disto, sabe-se, que Crotalus durissus terrificus na Amazônia ocorre somente em algumas áreas abertas de Humaitá, Serra do Cachimbo e Santarém (Melgarejo 2003). Mesmo sabendo-se do potencial de letalidade de uma serpente da espécie C. durissus terrificus com relação à quantidade de veneno existente em sua glândula, devemos recordar os estudos de Clarke & Clarke (1969), Silveira & Nishioka (1995), Bucaretchi et al (2002) e Melgarejo (2003, que tratam da relevante ocorrên-cia das chamadas "picadas secas" ou quando apenas parte do veneno é injetada, o que gera incertezas quanto a dose inoculada. A variação da concentração das toxinas em função de idade, peso, alimentação e distribuição geográfica da serpente dificulta ainda mais a referida projeção (Magro et al 2001, Furtado et al 2003.…”
Section: Achados De Necropsia E Histopatológicosunclassified